Bisubstrate inhibitors to target histone acetyltransferase 1. (30th January 2019) - Ngo, Liza; Brown, Tyler; Zheng, Yujun G.
Abstract: Developing selective enzyme inhibitors allows for the expansion of molecular toolboxes to investigate functions and activities of target enzymes. The histone acetyltransferase 1 (HAT1) is among the first histone acetyltransferase (HAT) enzymes that were discovered in the mid‐1990s; however, it remains one of the poorly studied enzymes in comparison with the other HATs. Although HAT1 has been linked to various disease states, no inhibitors have been reported to target HAT1. Here, we designed a set of peptide‐CoA conjugates as bisubstrate inhibitors of HAT1 with submicromolar potency. In particular, the bisubstrate inhibitor H4K12CoA exhibited a low K i value of 1.1 nM for HAT1. In addition, H4K12CoA was shown to be a competitive inhibitor with respect to both AcCoA and H4 peptide, suggesting a unique kinetic mechanism of HAT1 catalysis. Creating these submicromolar inhibitors offers mechanistic tools to better understand how HAT1 recognizes substrates and cofactors, as well as provides chemical leads to further develop therapeutic agents to target this important enzyme for disease therapy. Abstract : HAT1 is an important histone acetyltransferase in eukaryotic cells but its chemical probes are lacking. We designed bisubstrate conjugates as the first set of HAT1 inhibitors. In particular, the most potent inhibitor, H4K12CoA, exhibited a K i of 1.1 nM for HAT1. Generating these nanomolar inhibitors provides mechanistic tools for investigating functions of HAT1.